The Gasification Of Biomass: A Dynamic 3-D Coupling Study in Euler-Lagrange Discrete Element Methods (DEM) - Ismail, Tamer M.; Ding, Lu; Ramzy, Khaled; El-Salam, M. Abd (Journal of Environmental Accounting and Management, 2026)
The objective of this study is to understand the different phenomena related to the gasification of biomass in dense fluidized bed. It is interested, initially, in the phenomenological characterization of a dense shallow fluidized bed to evaluate the validity domain of the simulation tool used. A coupled transfers of a quasi-3-D system was studied to identify the most influential reaction mechanisms which best translated the gasification of the biomass. The gaseous phase was modeled as a continuum (Navier-Stokes), and the solid phase was processed via the discrete element method (DEM), including a collisional model called ``soft spheres". For this, it was relied upon a basic combustion reaction mechanism including both homogeneous and heterogeneous reactions in order to visualize the evolution of the diameter and density of biomass particles. This was with the aim to evaluate the effects and taking into account the coupling including mass transfer from the chemical model, heat transfer by providing gas heat input, and with the hydrodynamic transport particles entrained by the gas velocity. Among the results obtained, it was found the main characteristics of the dynamics of the bed both chemically and hydrodynamically. By comparison between experimental and simulated results, it can be obtained a little shift between the two signals, which was explained by measurement uncertainties, and the most important was the particle diameter measure (with 33% of possible error). Taking into account these uncertainties, the obtained quantitative values was in good agreement. Finally, the results from simulations were consistent with respect to chemical mechanisms implemented and the respect of the initial conditions considering the size and particle density evolution. Through parametric studies, a 3-D constitutive laws for dense fluidized beds at larger scale and a more detail study of biomass gasification to compare and validate data from the literature were developed.